PROCESS IMPLEMENTATION OF EARLY DETECTION OF EMOTIONAL MENTAL DEVELOPMENT OF PRE-SCHOOL CHILDREN AT GAMPING PUSKESMAS SLEMAN DIY - Tri Yubiah; Djauhar Ismail; Yuli Isnaeni; Yanti Yanti (Journal of Midwifery and Reproduction, 2020)
Early detection of children's emotional mental disorders is an activity or examination to find early emotional mental disorders of preschool children, this activity is not only carried out on children who are suspected of having a problem but is checked on all toddlers and preschool children regularly 2 times a year. Yogyakarta Special Region Province has a prevalence of mental emotional disorders above the average of 8.1% and is in the high category. This is to find out the parties involved in the process of implementing early detection of mental emotional disorders of preschool children at Puskesmas Gamping Sleman DIY. Descriptive qualitative research. The main informants were midwives, psychologists and doctors, while the supporting informants were kindergarten teachers. In-depth interviews were collected for the data collection. The results showed that the implementation, recapitulation, intervention, referral support and obstacles were still not optimal.